Doslej neznano pismo Louisa Adamiča iz zadnjega leta njegovega življenja - Glavan, Mihael (Dve domovini, 1996)
In 1995 two up to then unknown letters from Louis Adamič to Josip Vidmar were found among the papers of Josip Vidmar, kept by the National and University Library of Ljubljana. We are publishing them in their unabriged original form without any linguistic revisions. Of particular importance is the letter dated 15 January 1951, comprising 11 pages and describing Adamič's private psychophysical state, work on revising the book entitled The Eagle an the Roots as well as his views of the contemporary political situation in the USA and in Yugoslavia. The commentary to the publication analyses the contents in more detail and provides new insight into the relationships among the Slovene cultural personalities and politicians of the time.
Keywords: Adamič, Louis, 1898-1951; ameriški Slovenci; pisma; slovenski izseljenci; United States of America; ZDA